Comparative Evaluation of Gomori's Methenamine Silver and Periodic Acid-Schiff Staining Techniques for Detection of Candida Albicans in Oral Erosive Lichen Planus - Forooz Keshani; Neda Kargahi; Gholamreza Jahanshahi; Mohammad hosein Borzouzadeh (Journal of Mashhad Dental School, 2025)
Background: Lichen Planus is an immunological disease with a range of clinical manifestations includig, Erosive oral lichen planus which is usually acompany Candida infection, so identification and elimination is important due to the risks of cell changes.The present study was conducted with the aim of investigating, accuracy of Gomori's methenanin sliver (GMS) staining for the diagnosis of Candida albicans and comparing it with Periodic Acid-Shift (PAS) reaction.Methods and Materials: The present descriptive-analytical cross-sectional study was accomplished in the department of oral pathology. 30 samples with the final diagnosis of Erosive Lichen Planus were stained with GMS and PAS, and evaluated with three oral and maxillofacial pathologists synchronously. The presence of Candida fungi in the form of spores and hyphae together or individualy, was divided into 4 groups (No fungus present, only spores, few spores and hyphae, and many spores and hyphae) and evaluated. Statistical analysis was done by descriptive and analytical tests, linear regression and Fisher's exact test with SPSS software The significance level was 0.05, . Also Rock carve analysis was used to determine sensitivity and specificity.Results: : Respectively GMS staining showed the absence of spores and hyphae in 53.3% and PAS, 46.7% and only Spores in 20%  of GMS and 30% for PAS, few spores and hyphae in 26.7% for GMS and 23.3% of PAS (Pvalue<0.05).  The Rockwell plot based on the area under the curve (AUC) showed a large gap between sensitivity and specificity in the two staining methods, and the sensitivity and specificity of the PAS staining method were better than GMS.Conclusion: The power of detecting candidia fungi according to ROC carve with PAS staining was higher than the GMS staining. Age, gender, and location of the lesion had no effective the specificity and sensitivity of these staining methods.